Scientific criticism of “Unlawful prosecution regarding forest ecosystem destruction - Rodrigo Grazinoli Garrido (Revista Brasileira de Direito Processual Penal)
This scientific criticism was based on what was proposed in the article “Unlawful prosecution regarding forest ecosystem destruction,” aiming to expand its discussion, especially from a comparison between the Polish and the Brazilian reality. For this purpose, exploratory, documentary, and bibliographic research was carried out, allowing the recognition that the similarities in the prosecution of environmental crimes bring both countries closer together than they are further apart despite clear distinctions of environmental reality and criminal procedural diversity, especially concerning evidence.